Elaboración de una guía didáctica del parque nacional Cotopaxi para el área de campismo y recreación del laboratorio de interpretación turística para la carrera de ingeniería en ecoturismo de la ua-caren de la Universidad Técnica de Cotopaxi, (fase ii) - Carrillo Viracocha, Gessica Inés (2014)
A research study on the Development of a Didactic Guide on the Cotopaxi National Park and its Camping and Recreation Area of the Tourist Interpretation Laboratory was carried out in the Ecotourism Engineering Program, UA-CAREN at the Technical University of Cotopaxi. (Phase II). According to current research, it was possible to know some aspects, tourist attractions, and routes in the Cotopaxi National Park through a multimedia tool with information, images, and digital videos which strengthens the educational level. Method such as interview for park rangers, manager, and community as well as field visits to the different Nature and Cultural Resources were used for supporting the information. The Cotopaxi National Park encompasses an area of 33393 ha and extends into the Cotopaxi, Pichincha and Napo provinces. It has an altitudinal range from 3400 to 5897 meters above sea level, an average temperature of 7.7 °C, and snowfalls during May and September. It has four life zones (Montano Humid Forest – BmhM, Sub-andino Raining Highland – PpSA, Alpine Tropical Wet Paramus – TpA and Nival – N)….